Optimasi Distribusi Semen PT. XYZ dengan Modifikasi Model Transportasi - Aqidawati, Era Febriana (School of Industrial and System Engineering, Telkom University, 2017)
Transportation plays an important role for the industry because the producers have an interest in getting their goods transported to the customer on time, at the exact spot and goods are in good condition. Sari et al (2013) have optimized the transportation problem on the cement distribution system of PT. XYZ. In those article, optimization is done by minimizing transportation costs using the initial fiscal solution with the Least Cost method and calculating the optimal solution with potential method. However, in that calculation, the distance factor between the warehouse and the distribution and transport capacity is not considered. In fact, in distributing a product, the mileage factor becomes important enough to be considered because it involves many things in its operation. Therefore, in this article, the cement distribution cost will be optimized by using modified model of the transportation model used in Sari et al (2013).